EVALUASI PROGRAM PENGEMBANGAN DAN IMPLEMENTASI KURIKULUM TINGKAT SATUAN PENDIDIKAN (KTSP) - KUNANDAR KUNANDAR (Jurnal Evaluasi Pendidikan, 2011)
The purpose of this research is to measure the worth of the development and implementation of KTSP at SMPN 285 Pulau Untung Jawa in Administrative Regency of Kepulauan Seribu Province of DKI Jakarta. This evaluation research applied the CIPPO model evaluation which meant Context, Input, Process, Product, and Outcome. The result was categorized into three, i.e. high criteria, moderate criteria, and low criteria. The result also showed that (1) there were two aspects which had moderate level of actuality and one aspect with low actuality in sub evaluation of context, (2) there were sic aspects which had low level of actuality and two aspects with moderate level of actulity in sub evaluation of input, and (3) all aspects had low level of actuality in sub evaluation process, (4) all aspects had moderate level of actuality in sub evaluation of product, and (5) there were two aspects which had high level of actuality and one aspect with low level of actuality in sub evaluation of effect. The result of this study showed that the development and implementatio of KTSP in SMPN 285 Pulau untung Jawa at Kepulauan Seribu of DKI Jakarta Province was not optimal yet.